Immunogenicity of protein therapeutics - De Groot, Anne S.; Scott, David W. (Trends in immunology, 2007)
Protein therapeutics, such as monoclonal antibodies, enzymes and toxins, hold significant promise for improving human health. However, repeated administration of protein therapeutics, whether natural or recombinant, often leads to the induction of undesirable anti-drug antibodies (ADAs), which interfere with or neutralize the effect of the drug. Although an immune response to foreign proteins can be expected and is well understood, the basis for the development of responses to therapeutic autologous proteins is the subject of some debate. Inflammatory components of the drug delivery vehicle, T cell responses, T and B cell epitopes in the protein drug, and the associated B cell response are all targets for interventions aimed at reducing ADA responses. Here, we review some theories put forward to explain the immunogenicity of therapeutic proteins and describe some emerging protein-engineering approaches that might prevent the development of anti-drug antibodies.